"Is there anything else you would like to tell us" - Methodological issues in the use of free-text comments from postal surveys - Garcia, J; Evans, J; Reshaw, M (2004)
Free-text comments are often invited at the end of self-completion questionnaires, yet text books provide no guidance on how these might be used. We describe a variety of ways in which free-text comments can be used, drawing on two examples. An Audit Commission study of NHS maternity care included a national sample survey of 3570 women who gave birth in June and July 1995. At the end of the questionnaire women were asked: Is there anything else you would like to tell us about your care while you were pregnant or since you have had your baby. The United Kingdom Medical Careers Research Group conducts whole-cohort longitudinal studies of graduates from all UK medical schools. At the end of each survey doctors are invited to write comments on "any aspect of your training, career choices or work". The authors discuss the inherent limitations of free-text comments, the relative merits of quantifying the frequencies of themes, and the ways in which free-text comments can be used to enhance survey analysis. They conclude that while free-text comments are no substitute for properly designed research, they are nevertheless valuable in understanding and illustrating participants' survey responses, and in suggesting topics for further research.